2015
DOI: 10.1111/hdi.12370
|View full text |Cite
|
Sign up to set email alerts
|

Our experience in using the brachial venae comitantes as a native vascular access for hemodialysis

Abstract: A native arteriovenous fistula is the preferred vascular access for patients on long-term hemodialysis. In the absence of suitable superficial veins, the deep venous system can be used. We intend to present our experience in using the brachial venae comitantes (VC) to create a native arteriovenous fistula. From January 2012 to December 2014, we utilized the brachial vena comitantes to create 12 arteriovenous fistulae. Data from these 12 subjects were analyzed retrospectively to produce this case series. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…5,12 The other series exhibited higher rates for BB-AVFs, ranging between 14.9% and 52.9%. 7,8,10,11,[13][14][15][16][17][18][19] The data reported in Fig 4 and Supplementary Table II (online only) also provide evidence that BB-AVGs performed equally well or even better than BB-AVFs in terms of access patency. Most of the studies on BB-AVFs showed a secondary patency below the median survival of 3 years expected by the KDOQI guidelines.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…5,12 The other series exhibited higher rates for BB-AVFs, ranging between 14.9% and 52.9%. 7,8,10,11,[13][14][15][16][17][18][19] The data reported in Fig 4 and Supplementary Table II (online only) also provide evidence that BB-AVGs performed equally well or even better than BB-AVFs in terms of access patency. Most of the studies on BB-AVFs showed a secondary patency below the median survival of 3 years expected by the KDOQI guidelines.…”
Section: Discussionmentioning
confidence: 64%
“…25,42 As an alternative option for patients with poor superficial veins, many authors have proposed creating an upper arm AVF by elevating or transposing the brachial vein. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] We therefore compared our results with published series on BB-AVGs and BB-AVFs. As depicted in Fig 2, BB-AVFs were less likely than BB-AVGs to be used successfully for HD.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies, including 431 cases of arteriovenous fistula creation using the brachial vein, were selected from a pool of 305 studies. 10–24 Of these, 78 cases (23%) were one-staged procedures and 258 cases (77%) were two-staged procedures. Three studies were excluded because they included less than five patients in their studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The use of the brachial vein for vascular access is not popular among vascular surgeons, but may be a good hypothesis for a permanent autologous access. In the review of the literature, we identified 11 studies, between 2005 and 2017, with a total of 330 brachio‐brachial AVF (1 or 2‐stage) . This type of fistula can be created in 1 or 2‐stage, and it is a viable alternative to the arteriovenous graft in patients with inadequate superficial venous anatomy, especially in access‐native patients .…”
Section: Discussionmentioning
confidence: 99%
“…In the review of the literature, we identified 11 studies, between 2005 and 2017, with a total of 330 brachio-brachial AVF (1 or 2-stage). 6,7 This type of fistula can be created in 1 or 2-stage, and it is a viable alternative to the arteriovenous graft in patients with inadequate superficial venous anatomy, especially in access-native patients. 7 Our solution to drain the cephalic radio veins through the brachial vein may allow the creation of the brachio-brachial fistula in one stage.…”
Section: Discussionmentioning
confidence: 99%